Ex-vivo preservation technique of autologous bone flap in resource limited settings: Retrospective analysis of outcome based on single institute of Nepal - Joshi, Sumit; Paudel, Prakash; Karki, Prasanna; Bikram Shah, Dambar; Raman Sharma, Gopal (Nepal Journal of Neuroscience, 2022)
Objective: Ex-vivo preservation of autologous bone flap for cranioplasty involves various techniques but there are no fixed guidelines as preservation time, temperature ,technique differs. It was preserved submerging in the mixture of 10% betadine and 80 % ethyl alcohol solution in an airtight container in refrigerator at constant temperature of 0 ﹾ C and was autoclaved 1 hour before reimplantation. The Primary objective of the study is to analyze Surgical site infection (SSI) ,secondary its association with dependent variables age,sex,mode of injury, number of procedure performed . Materials and methods: This is a retrospective study conducted in Nepal Mediciti hospital from September 2017 to November 2019 .Data of all patients who underwent cranioplasty was reviewed from medical record and U/L autologous bone cranioplasty preserved with this technique were included and other were excluded from the study.The primary outcome SSI was classified according to guidelines of the centers of disease control(CDC) and stablished with organism isolated in the culture. Results: Only 66 out of 78 cranioplasty was included in this study .The majority was male 83.3%.The mean age was 37.16(standard deviation [SD]±14.58).The SSI was 7.5% and was associated with number of procedures performed (p0.08).RTA was major cause of cranioplasty in 60.61%. Conclusion: Ex-vivo preservation of autologous bone flap for cranioplasty with this technique is safe to be applied in resource limited settings as it can produce similar results as other techniques.